Asksia AI LOGO

Sia

文凱's Question
Math
Posted 8 months ago

胡算 f(z)=C4z(z+1)(z1)(z3)dzf(z)=\oint_{C} \frac{4 z}{(z+1)(z-1)(z-3)} d z,
(a) 若封閉曲缐 C\mathrm{C} 分別為: z=2|z|=2, 則 f(z)=f(z)=
(b) 若封閉曲缐 C 分別為: z=4|z|=4, 則 f(z)=f(z)=
Sign in to unlock the answer
Answer from Sia
Posted 8 months ago
Solution by Steps
step 1
We start by identifying the poles of the integrand f(z)=4z(z+1)(z1)(z3)f(z) = \frac{4z}{(z+1)(z-1)(z-3)}. The poles are at z=1z = -1, z=1z = 1, and z=3z = 3
step 2
For part (a), the path of integration is z=2|z| = 2. We need to check which poles lie inside this circle. The poles z=1z = -1 and z=1z = 1 lie inside z=2|z| = 2, but z=3z = 3 does not
step 3
We use the residue theorem to evaluate the integral. The residue theorem states that Cf(z)dz=2πiRes(f,zk)\oint_{C} f(z) \, dz = 2\pi i \sum \text{Res}(f, z_k), where zkz_k are the poles inside CC
step 4
Calculate the residues at z=1z = -1 and z=1z = 1. For z=1z = -1, the residue is Res(f,1)=limz1(z+1)4z(z+1)(z1)(z3)=4(1)(2)(4)=12\text{Res}(f, -1) = \lim_{z \to -1} (z + 1) \frac{4z}{(z+1)(z-1)(z-3)} = \frac{4(-1)}{(-2)(-4)} = \frac{1}{2}
step 5
For z=1z = 1, the residue is Res(f,1)=limz1(z1)4z(z+1)(z1)(z3)=4(1)(2)(2)=1\text{Res}(f, 1) = \lim_{z \to 1} (z - 1) \frac{4z}{(z+1)(z-1)(z-3)} = \frac{4(1)}{(2)(-2)} = -1
step 6
Sum the residues: Res(f,1)+Res(f,1)=121=12\text{Res}(f, -1) + \text{Res}(f, 1) = \frac{1}{2} - 1 = -\frac{1}{2}
step 7
Apply the residue theorem: f(z)=2πi(12)=πif(z) = 2\pi i \left( -\frac{1}{2} \right) = -\pi i
step 8
For part (b), the path of integration is z=4|z| = 4. All three poles z=1z = -1, z=1z = 1, and z=3z = 3 lie inside this circle
step 9
Calculate the residue at z=3z = 3. The residue is Res(f,3)=limz3(z3)4z(z+1)(z1)(z3)=4(3)(4)(2)=1.5\text{Res}(f, 3) = \lim_{z \to 3} (z - 3) \frac{4z}{(z+1)(z-1)(z-3)} = \frac{4(3)}{(4)(2)} = 1.5
step 10
Sum the residues: Res(f,1)+Res(f,1)+Res(f,3)=121+1.5=1\text{Res}(f, -1) + \text{Res}(f, 1) + \text{Res}(f, 3) = \frac{1}{2} - 1 + 1.5 = 1
step 11
Apply the residue theorem: f(z)=2πi(1)=2πif(z) = 2\pi i (1) = 2\pi i
Answer
(a) f(z)=πif(z) = -\pi i
(b) f(z)=2πif(z) = 2\pi i
Key Concept
Residue Theorem
Explanation
The residue theorem allows us to evaluate complex integrals by summing the residues of the integrand's poles inside the contour of integration.

Not the question you are looking for? Ask here!

Enter question by text

Enter question by image

Unlock Smarter Learning with AskSia Super!

Join Super, our all-in-one AI solution that can greatly improve your learning efficiency.

30% higher accuracy than GPT-4o
Entire learning journey support
The most student-friendly features
Study Other Question